Innovative Supercritical Particle Formation for the Sustainable Manufacturing of Advanced Drug Delivery Systems - Daniele Sofia; Massimo Moffa; Paolo Trucillo (Chemical Engineering Transactions, 2025)
The Supercritical Particle Formation (SPAF) process represents a significant advancement in the development of drug delivery systems for both pharmaceutical and nutraceutical applications. Traditional manufacturing methods often face challenges such as residual solvent contamination, low reproducibility, and limited versatility in bioactives encapsulation. On the contrary, SPAF exploits the benefits deriving from the use of supercritical fluids to remove solvent residue, thus resulting in a highly efficient, eco-friendly process, guaranteeing the coupling of several hydrophilic and lipophilic compounds with polymeric or lipidic carriers. This technique improves the yield at industrial level, without losing control over particle size distribution and morphology, release profile and cell bioavailability of active ingredients. The improved stability of SPAF products is guaranteed by the addition of a process unit, made of several freeze-dryers working in parallel, to transform the liquid suspension of carriers into powder stable over 2 years. The synergy between supercritical particle formation and lyophilization offers a successful platform to produce high-quality, ready-to-market drug delivery systems with improved pharmacokinetic properties. This study highlights yield, profit and environmental benefits of SPAF, positioning it as a valid alternative to conventional production techniques nowadays utilized by companies.